2009
DOI: 10.1074/jbc.m109.037184
|View full text |Cite
|
Sign up to set email alerts
|

Activating Mutations of the TRPML1 Channel Revealed by Proline-scanning Mutagenesis

Abstract: The mucolipin TRP (TRPML) proteins are a family of endolysosomal cation channels with genetically established importance in humans and rodent. Mutations of human TRPML1 cause type IV mucolipidosis, a devastating pediatric neurodegenerative disease. Our recent electrophysiological studies revealed that, although a TRPML1-mediated current can only be recorded in late endosome and lysosome (LEL) using the lysosome patch clamp technique, a proline substitution in TRPML1 (TRPML1 V432P) results in a large whole cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
110
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 45 publications
3
110
1
Order By: Relevance
“…Likewise, C430P and C431P mutants were found to be constitutively active. In contrast, V436P rendered the channel completely inactive 13 . Similarly, V436C may render the channel inactive by a mechanism which cannot be overcome by compounds of the SF-22 type.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, C430P and C431P mutants were found to be constitutively active. In contrast, V436P rendered the channel completely inactive 13 . Similarly, V436C may render the channel inactive by a mechanism which cannot be overcome by compounds of the SF-22 type.…”
Section: Discussionmentioning
confidence: 99%
“…TMD5 mutations in TRPML channels have recently been shown to have a critical impact on TRPML channel opening (varitint-waddler mutant isoforms and analogues). Thus, mutation of V432 to proline renders TRPML1 constitutively active 10,13 . Likewise, C430P and C431P mutants were found to be constitutively active.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using whole-endolysosome recordings, we recently found that TRPML1 conducts both Ca 2+ and Fe 2+ , and can be activated specifically by PI(3,5)P 2 but not other phosphoinositides (12,16,17). Interestingly, TRPML1 can also be detected in nonlysosome cellular compartments, in particular, the PM, upon exocytosis from the Golgi apparatus (the biosynthetic pathway) (13,14) or the lysosome (lysosomal exocytosis) (18,19). Indeed, when lysosomal exocytosis was dramatically increased by a constitutively active TRPML1 mutant (TRPML1 Va ), large whole-cell TRPML1 currents were detected (18).…”
Section: Trp Channel | Mucolipinmentioning
confidence: 98%
“…Four linker helices surround the S6 bundle crossing and stabilize the closed channel pore. It is interesting to note that several gain-of-function mutations similar to the V432P varitint-waddler phenotype 15,27-29 have been identified on S5 in a proline-scanning mutagenesis study 30 , including R427P, C430P and C431P, which are all clustered at the interaction interface between the S5 and S4-S5 linker (Fig. 4c).…”
Section: Main Textmentioning
confidence: 99%